The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s40708-016-0051-5
|View full text |Cite
|
Sign up to set email alerts
|

Familiarity effects in EEG-based emotion recognition

Abstract: Although emotion detection using electroencephalogram (EEG) data has become a highly active area of research over the last decades, little attention has been paid to stimulus familiarity, a crucial subjectivity issue. Using both our experimental data and a sophisticated database (DEAP dataset), we investigated the effects of familiarity on brain activity based on EEG signals. Focusing on familiarity studies, we allowed subjects to select the same number of familiar and unfamiliar songs; both resulting datasets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(50 citation statements)
references
References 30 publications
3
47
0
Order By: Relevance
“…Momennezhad and A [12] used wavelet transform for feature extraction, and the accuracy rates of the two-class recognition of valence and arousal degree were 0.73 and 0.77, respectively; Lin Jingxin [13][14][15][16] In order to solve the above problems, this paper proposes RMFS algorithm [17][18][19]. This may be achieved by reducing the feature dimension, eliminating the redundant, prioritizing weighting channels and improving the accuracy of emotional recognition for being weighted formula is optimized for the characteristics of the different subjects set of weights, thus optimizing the matching characteristics of the subjects groups.…”
Section: Introductionmentioning
confidence: 99%
“…Momennezhad and A [12] used wavelet transform for feature extraction, and the accuracy rates of the two-class recognition of valence and arousal degree were 0.73 and 0.77, respectively; Lin Jingxin [13][14][15][16] In order to solve the above problems, this paper proposes RMFS algorithm [17][18][19]. This may be achieved by reducing the feature dimension, eliminating the redundant, prioritizing weighting channels and improving the accuracy of emotional recognition for being weighted formula is optimized for the characteristics of the different subjects set of weights, thus optimizing the matching characteristics of the subjects groups.…”
Section: Introductionmentioning
confidence: 99%
“…Many existing methods implemented facial expression, speech signals, and self-ratings to classify emotions [3], [4]. However, the systems used in these existing methods usually fail to acknowledge all the detailed emotional inputs for processing, such as the hand gestures or the tone of the voice, thus leading to vague and biased outcome [3].…”
Section: Introductionmentioning
confidence: 99%
“…However, the systems used in these existing methods usually fail to acknowledge all the detailed emotional inputs for processing, such as the hand gestures or the tone of the voice, thus leading to vague and biased outcome [3]. Some approaches used subjective measurement that can affect the end result as the presence of anomalous trials can be significant [4]. After the high influence of Electroencephalogram (EEG) signals on the field of research, it was observed that human emotion can be represented more accurately with EEG signals than with facial gestures, speech signals, or self-reporting information [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies [3,4] show that the assessment of the degree of familiarity with the presented material allows much more accurate assessment of the emotional state. Dynamic evaluation of familiarity with the materials, also allows us to estimate the speed of the skills mastering, which require repetition of the material, as shown in [5] using the example of evaluating familiarity with integrated development environments.…”
Section: Introductionmentioning
confidence: 99%